Characterization of the wear resistant aluminum oxide - 40% titaniumdioxide coating - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Plasma spray coatings play an important role in the design of surface properties of engineering components in order to increase their durability and performance under different operating conditions. Coatings are the most often used for wear resistance. This paper presents the microstructure and mechanical properties Al2O3_40wt.%TiO2 coating resistant to dry friction slide, grain abrasion and erosion of particles at operating temperatures up to 540°C. In order to obtain the optimal characteristics of coating was performed optimization of deposition parameters. The powder Al2O340wt.%TiO2 is deposited atmospheric plasma spraying (APS) process with a plasma current of 700, 800 and 900A. Evaluate the quality of the coating Al2O340wt.%TiO2 were made on the basis of their hardness, tensile bond strength and microstructure. The best performance showed the deposited layers with 900A. The morphology of the powder particles Al2O340wt.%TiO2 was examined with SEM (Scanning Electron Microscope). Microstructure of the coatings was examined by light microscopy. Analysis of the deposited layers was performed in accordance with standard Pratt & Whitney. Evaluation of mechanical properties of the layers was done by examining HV0.3 microhardness and tensile strength of the tensile testing. Studies have shown that plasma currents significantly affects the mechanical properties and microstructure of coatings which are of crucial importance for the protection for components subjected to wear